Extended follow-up of neurological, cognitive, behavioral and academic outcomes after severe abusive head trauma. (January 2016) - Lind, Katia; Toure, Hanna; Brugel, Dominique; Meyer, Philippe; Laurent-Vannier, Anne; Chevignard, Mathilde
Abstract: Studies about long-term outcome following abusive head trauma (AHT) are scarce. The aims of this study were to report long-term neurological, cognitive, behavioral and academic outcomes, ongoing treatments and/or rehabilitation, several years after AHT diagnosis, and factors associated with outcome. In this retrospective study, all patients admitted to a single rehabilitation unit following AHT between 1996 and 2005, with subsequent follow-up exceeding 3 years, were included. Medical files were reviewed and a medical interview was performed with parents on the phone when possible. The primary outcome measure was the Glasgow Outcome Scale (GOS). Forty-seven children (out of 66) met the inclusion criteria (mean age at injury 5.7 months; SD = 3.2). After a median length of follow-up of 8 years (range 3.7–12), only seven children (15%) had "good outcome" (normal life – GOS I) and 19 children (40%) presented with severe neurological impairment (GOS III and IV). Children sustained epilepsy (38%), motor deficits (45%), visual deficit (45%), sleep disorders (17%), language abnormalities (49%), attention deficits (79%) and behavioral disorders (53%). Most children (83%) had ongoing rehabilitation. Only 30% followed a normal curriculum, whereas 30% required special education services. Children with better overall outcome (GOS I and II) had significantly higher educated mothers than those with worse outcomes (GOS III and IV): graduation from high school 59% and 21% respectively ( p  = 0.006). This study highlights the high rate of severe sequelae and health care needs several years post-AHT, and emphasizes the need for extended follow-up of medical, cognitive and academic outcomes.